Is time important in response of morpho-physiological parameters in Withania coagulans L. landraces to water deficit stress? - Ghanbari, Majid; Modarres-Sanavy, Seyed Ali Mohammad; Mokhtassi-Bidgoli, Ali (Industrial crops and products, 2019)
•This is the first report of Withania coagulans response to G × E interaction.•Distance between stress time and photosynthesis indices measurements is important.•Values for Fv/Fm in Fanuj, F0 and ФPSII decreased with increasing stress severity.•Photosynthesis rate declined and leaf greenness increased with the onset of drought.•According to results, W. coagulans can be called "Xerophytes Camel". Withania coagulans is one of the most important medicinal species of the Solanaceae which has pharmacological properties for future research in drug development. Photosynthesis and morphological parameters in response to drought of this species have not been investigated as yet, though the issue is of interest. The factorial combination of four water deficit stress (20% (un-stressed control), 30%, 40% and 50% of FC depletion) and four landraces of W. coagulans (Fanuj, Khash, Saravan and Sarbaz) were laid out in a randomized complete design in a phytotron over the course of 180 days. The first, second, third and fourth samplings were performed every 45 day after imposing the treatments (DAT). The results demonstrated that increase in the water deficit stress levels, decreased minimal fluorescence (F0), leaf greenness, photosynthesis rate, plant height, leaf area, dry weight and quantum yield of PSII photochemistry )ФPSII(in all landraces and maximum photochemical efficiency of PSII (Fv/Fm) in Fanuj, but increased non-photochemical quenching)NPQ(and Fv/Fm in Saravan and Sarbaz landraces. The W. coagulans landraces such as Fanuj with the highest vector loadings of ФPSII at 135 and 180 DAT and Fv/Fm at 45 DAT and Sarbaz with the highest vector loading of F0 at 45 DAT were found suitable for unstressed and severe stress conditions, respectively. Among the chlorophyll fluorescence and morphological parameters, total dry weight had the significant positive correlations with plant height, leaf area and F0 at 45 DAT. Thus, this study indicated chlorophyll florescence should be measured at different phases and future studies should focus on the sensitivity of these parameters to detect potential times among subjects of different stresses. These parameters are easy, cheap, efficient and reliable physiological characteristics which can be used to guide the breeding of new resistant genotypes. According to results, W. coagulans can be called "Xerophytes Camel".